2016
DOI: 10.1080/02692171.2015.1105938
|View full text |Cite
|
Sign up to set email alerts
|

Determinants and value relevance of UK CEO pay slice

Abstract: This paper studies the CEO Pay Slice (CPS) of UK listed firms during the period 2003 to 2009. We investigate the determinants of CPS. We study the links between CPS and measures of firm performance. We find that firms with higher levels of corporate governance ratings and those with more independent boards tend to have higher CPS. In addition, we find that CEOs are more likely to receive lower compensation when they chair the board and when they work in firms with large board size. We also find that higher CPS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 52 publications
1
4
0
Order By: Relevance
“…In addition, 14 our proxy for CEO power better captures top managerial talent and the concentration of decision making. Our finding is consistent with that of Al-Najjar et al (2016), suggesting that powerful CEOs have a higher CPS because of their superior talent and skills, which leads the firms they manage to reach high levels of financial performance and to engage in environmental actions.…”
Section: Multivariate Regression Analysessupporting
confidence: 89%
See 2 more Smart Citations
“…In addition, 14 our proxy for CEO power better captures top managerial talent and the concentration of decision making. Our finding is consistent with that of Al-Najjar et al (2016), suggesting that powerful CEOs have a higher CPS because of their superior talent and skills, which leads the firms they manage to reach high levels of financial performance and to engage in environmental actions.…”
Section: Multivariate Regression Analysessupporting
confidence: 89%
“…This suggests that the power of CEOs is attributable to their greater managerial skills rather than their rent-extracting abilities. Al-Najjar et al (2016) also show that higher CPS levels indicate a CEO's talent and ability to foster stronger firm performance.…”
Section: Ceo Power and Ep: Exploring The Role Of Financial Performancementioning
confidence: 80%
See 1 more Smart Citation
“…Table 2 shows an overview of the board's characteristics for the sample firms during the study period (2004)(2005)(2006)(2007)(2008)(2009)(2010)(2011)(2012)(2013) Two dummy variables to control for insurance line of business; one to indicate selling life insurance and the other to indicate selling nonlife insurance. Therefore, life dummy is assigned "1" and non-life dummy is assigned "0" for life insurance firms, while for non-life insurance firms, non-life dummy is assigned "1" and the other one "0" Al-Najjar and Hussainey (2016) Listing Status (Listed, Non-Listed)…”
Section: Descriptive Statisticsmentioning
confidence: 99%
“…Findings of Liu et al (2020) suggest that as firm leverage reaches a certain level, further incentive cannot motivate the executives to adopt more aggressive debt policy. Alternatively, a few studies such as Al-Najjar et al (2016) and Elsayed and Elbardan (2018) have observed an insignificant relation between leverage and compensation.…”
Section: Literature Reviewmentioning
confidence: 99%